2021
DOI: 10.3389/fmed.2021.683250
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, Leptin, and IGF-1 Are Useful Diagnostic and Stratification Biomarkers of NAFLD

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease where liver biopsy remains the gold standard for diagnosis. Here we aimed to evaluate the role of circulating adiponectin, leptin, and insulin-like growth factor 1 (IGF-1) levels as non-invasive NAFLD biomarkers and assess their correlation with the metabolome.Materials and Methods: Leptin, adiponectin, and IGF-1 serum levels were measured by ELISA in two independent cohorts of biopsy-proven obese NAFLD patients and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…Its levels can be lowered with the increase of pro-inflammatory cytokines. In addition to contributing to inflammation, such adipokine induces thermogenesis and fatty acid oxidation in skeletal muscle and liver [ 64 , 66 ]. Moreover, adiponectin may contribute to keeping HSCs in their quiescent state [ 65 ].…”
Section: Organokinesmentioning
confidence: 99%
“…Its levels can be lowered with the increase of pro-inflammatory cytokines. In addition to contributing to inflammation, such adipokine induces thermogenesis and fatty acid oxidation in skeletal muscle and liver [ 64 , 66 ]. Moreover, adiponectin may contribute to keeping HSCs in their quiescent state [ 65 ].…”
Section: Organokinesmentioning
confidence: 99%
“…Although the results of our study do not have clear implications for clinical practice, they may be important for guiding future mechanistic and intervention studies. In fact, the evidence from this and other studies [11][12][13][14][15][16]18] suggests a possible role of decreased adiponectin levels in the pathophysiology of NAFLD, thus underlining the need for future large-scale studies assessing the predictive as well as the therapeutic role of this adipokine in the spectrum of NAFLD. Additionally, these results may encourage the designing of diagnostic accuracy studies to examine whether plasma adiponectin levels may contribute (alone or in combination with other biomarkers) to the achievement of a non-invasive diagnosis of liver fibrosis.…”
Section: Discussionmentioning
confidence: 74%
“…In recent years, many observational studies [11][12][13][14][15][16] and some meta-analyses [17] have reported that lower plasma adiponectin levels are significantly associated with the presence and severity of NAFLD, especially in patients without T2DM, thereby suggesting that hypoadiponectinemia might represent a risk factor for NAFLD. However, little information is available to date on the association between lower plasma adiponectin levels and the presence of NAFLD or NASH in patients with T2DM [18].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired hepatic insulin signaling [91], triglycerides, and increased expression of gluconeogenic enzymes have been reported for MO non-human primate offspring [31]. In addition to adiponectin, serum leptin concentrations are increased in NAFLD subjects [92], suggesting a potential AT dysfunction prior to hepatic fat accumulation, which results in new metabolic homeostasis stimulated by adipokines' levels. HepG2 leptin treatment led to decreased expression of low-density lipoprotein (LDL) receptors and decreased LDL uptake, with augmented proprotein convertase subtilisin/kexin type 9 (PCSK9), which proved essential for the observed response [93].…”
Section: Impact Of Mo Programming Of Endocrine-metabolic Axis Dysregu...mentioning
confidence: 99%